Filtering Touch: An Ethnography of Dirt, Danger, and Industrial Robots. (February 2022) - Barker, Ned; Jewitt, Carey
"Industry 4.0" marks the advent of a new wave of industrial robotics designed to bring increased automation to "extreme" touch practices and enhance productivity. This article presents an ethnography of touch in two industrial settings using fourth generation industrial robots (a Glass Factory and a Waste Management Center) to critically explore the social and sensorial implications of such technologies for workers. We attend to manifestations of dirt and danger as encountered through describing workers' sensory experiences and identity formation. The contribution of the article is two-fold. The first is analytical through the development of three "filters" to grasp the complexity of the social and sensorial dynamics of touch in situ while tracing dispersed mediating effects of the introduction of novel technologies. The second is empirical, teasing out themes embedded in the sociosensorial dynamics of touch that intersect with gender, ethnicity, and class and relate to the technological mediation of touch.